Mechanism of atrazine migration and diffusion control in soil by clay matrix composites - Xiangyu Wang; Qiang Fu; Tianxiao Li; Renjie Hou; Mo Li; Dong Liu; Fanying Kong; Mingxuan Liu; Shuqi Dong (Ecotoxicology and Environmental Safety)
The study investigates the mechanisms of atrazine (ATZ) migration control in cold-zone black soil subjected to freeze-thaw cycles (FC). Current remediation technologies face several challenges, including destabilization of soil structure due to freeze-thaw cycles, unknown environmental effects, insufficient long-term effectiveness, and a lack of multifunctional materials and methods to quantify the migration capacity of ATZ in cold climate zones. In this study, three major problems of soil structure optimization, competitive adsorption enhancement and quantification of migration patterns in FC environments were solved through the preparation of clay-based composites (Sep/BC) combined with soil column simulation tests and isothermal adsorption tests. The results of the study showed that the application of Sep/BC material optimized the soil physico-chemical properties: it increased the soil CEC (19.43 %), pH (7.14), EC (62.50 μs/cm). Sep/BC increased the saturated hydraulic conductivity of the soil by 42.89 % and porosity by 2.81 %, which resulted in a reduction of the ATZ leaching rate by 49 %. The composites had a maximum adsorption capacity of 160.08 mg/g after FC activation, combining iron-catalyzed degradation with competitive resistance to organic matter. The established migration prediction equation (R²= 0.89) revealed soil hydraulic conductivity, STPSD and organic carbon as the main controlling factors regulating ATZ migration. Sep/BC maintains optimal structural stability in FC and achieves a synergistic fixation effect with TOC/Fe mobility as low as 0.27/0.034. This study provides a solution to synchronise soil improvement and pesticide blocking and control for farmland in cold regions, which is of great practical significance for ensuring groundwater safety and sustainable use of black soil.